Subsurface geodiversity determines shrub resilience vs. mortality under long-term droughts in the Israeli Negev drylands - Basson, Uri; Argaman, Eli; Yizhaq, Hezi; Xu, Chi; Xu, Zhiwei; Stavi, Ilan (Frontiers in Environmental Science, 2023)
Shrubs, encompassing important ecosystem engineers in dryland environments, have experienced mass mortality due to long-term droughts across the northwestern Israeli Negev. This massive die-back, which has particularly affected the predominant shrub species Noaea mucronata, predominates edaphically homogeneous (low geodiversity) hillslopes, and is minor in edaphically heterogeneous (high geodiversity) hillslopes. While the homogeneous hillslopes encompass a thick and non-stony soil layer, the heterogeneous hillslopes are composed of a thin, stony layer that overlies weathered, chalky bedrock. The objective of this geophysical study was to assess the subsurface and bedrock characteristics, and its effect on shrub durability vs. mass mortality in a dryland ecosystem. A combination of 2D and 3D Ground Penetrating Radar (GPR) imaging and Frequency Domain Electromagnetics (FDEM) was applied. For the GPR procedure, the 2D and 3D reflection imaging was dominated by different dielectric permittivities (dielectric constants) of layers and changes in soil-rock-water content. For the FDEM procedure, the soil-rock electrical properties, alongside the concentration of dissolved salts, determined the measured electrical conductivity (EC). The results show substantial differences in EC values between the homogeneous and heterogeneous hillslopes, which are attributed to differences in the soil-rock interface, soil-water content, and salts concentration. Overall, the much greater EC values of the soil-rock interface in the heterogeneous hillslopes are expected to adversely affect shrub vitality. However, the greater shrub vitality in these hillslopes is likely attributed to the fractured and weathered chalky underground, which retains moisture in pockets or micro-aquicludes that increase water availability for the shrubs. Under these better habitat conditions of the heterogeneous hillslopes, the high EC values do not limit shrub survival or growth. At the same time, the absence of such water pockets in the thick soil layer of the homogeneous hillslopes imposes severe stress under long-term drought conditions, resulting in shrub die-off. This study illustrates the vital role of subsurface geodiversity in determining the resilience of dryland ecosystems to droughts and climatic change.